Basic knowledge level of oral health in teenagers and their mothers - Mirella Alejandra Lavastida Fernández; Estela de los Ángeles Gispert Abreu (Editorial Ciencias Médicas, 2015)
Introduction: knowledge of oral health is important in mothers and children for the adoption of health promotion strategies, and risk prevention of oral diseases. Objectives: identify the relation between levels of knowledge of basic oral health for mother-adolescent children. Method: a study was carried out in two stages, a descriptive and a traverse court analytic, on 167 adolescents- out of a universe of 561-, aging 12-14 years at junior high "An", Playa municipality. They were randomly selected with their mothers. The information was collected from questionnaires. The frequency of children and mothers was estimated according to level of knowledge, 95 % of confidence intervals (CI) reliability. The odds ratio (OR) was also analyzed in low level of awareness in children according to variables of mothers (their level of education which was taken as a confounding variable) by Wald logistic regression step backwards with significance of p£0,05, and the instrumental value of mothers knowledge in the diagnosis of their children by sensitivity, specificity, and ROC curve. Results: 85.6 % of adolescents and 91.6 % of mothers had a high level of knowledge, the children level of knowledge was significantly associated with their mothers (p£0,000) with OR 39.486 (9.763 to 159.71), even after correcting the association it remained at 37,500 (2.771 to 507.475), sensitivity was 97.9 % (97.5 to 98.3) and the diagnostic accuracy was 71.9 % (59.7 to 84.0). Conclusions: mother's level of knowledge is a tool to identify their children´s, so the argument is reinforced for including mothers in strategies to preserve oral health in adolescents.